2020
DOI: 10.1002/anie.202000961
|View full text |Cite
|
Sign up to set email alerts
|

A Glutathione Activatable Ion Channel Induces Apoptosis in Cancer Cells by Depleting Intracellular Glutathione Levels

Abstract: Cancer cells use elevated glutathione (GSH) levels as an inner line of defense to evade apoptosis and develop drug resistance.Inthis study,wedescribe anovel 2,4-nitrobenzenesulfonyl (DNS) protected 2-hydroxyisophthalamide system that exploits GSH for its activation into free 2-hydroxyisophthalamide forming supramolecular M + /Cl À channels.Better permeation of the DNS protected compound into MCF-7 cells compared to the free 2-hydroxyisophthalamide and GSHactivatable ion transport resulted in higher cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(44 citation statements)
references
References 62 publications
2
42
0
Order By: Relevance
“…The results suggested that compound 1 displayed enhanced cytotoxicity with an increase in concentration of the compound giving IC 50 values of 15 and 20 μ m for MCF‐7 and HeLa cells, respectively. The higher IC 50 value of the esterase activatable compound (IC 50 value of 15 μ m for MCF‐7 cells) compared to our previously reported glutathione activatable compound (IC 50 value of 1 μ m for MCF‐7 cells) may be corroborated to 1) better permeability of the 2,4‐dinitrobenzenesulfonyl (DNS) linked protransporter and 2) better cleavability of DNS group (i.e., faster activation). The effect of by‐products (formaldehyde and pivalic acid as 4‐methoxyphenol is proved to be nontoxic to cells) generated in situ on cell viability was evaluated independently in MCF‐7 cells; compound 6 showed negligible cytotoxicity compared to 1 (Figure S2).…”
Section: Figurementioning
confidence: 47%
See 1 more Smart Citation
“…The results suggested that compound 1 displayed enhanced cytotoxicity with an increase in concentration of the compound giving IC 50 values of 15 and 20 μ m for MCF‐7 and HeLa cells, respectively. The higher IC 50 value of the esterase activatable compound (IC 50 value of 15 μ m for MCF‐7 cells) compared to our previously reported glutathione activatable compound (IC 50 value of 1 μ m for MCF‐7 cells) may be corroborated to 1) better permeability of the 2,4‐dinitrobenzenesulfonyl (DNS) linked protransporter and 2) better cleavability of DNS group (i.e., faster activation). The effect of by‐products (formaldehyde and pivalic acid as 4‐methoxyphenol is proved to be nontoxic to cells) generated in situ on cell viability was evaluated independently in MCF‐7 cells; compound 6 showed negligible cytotoxicity compared to 1 (Figure S2).…”
Section: Figurementioning
confidence: 47%
“…The inactive form, 1 , of the channel‐forming molecule was designed by connecting methyl pivalate at the C‐2 position of N 1 , N 3 ‐dihexyl‐2‐hydroxyisophthalamide ( 2 ) so that the system fails to self‐assembly properly (Figure ). We have recently demonstrated ion channel formation by 2 activated by glutathione . Such ion channel activation was confirmed by using MCF‐7 and INS‐1E cells.…”
Section: Figurementioning
confidence: 64%
“…[14,15] Talukdar has recently reported GSH switchable synthetic ion channels capable of achieving transmembrane M + /Cl À symport in presence of elevated levels of GSH. [16] These systems induced caspase-dependent apoptosis in MCF-7 cells which was correlated with the resulting cytotoxicity in rat insulinoma cells (INS-1E), which have high levels of intracellular GSH. [16] Inspired by the high affinity of thiols,s uch as GSH, for gold as exemplified by Chess eminal work on switch-on fluorescent probes [17] and the reported anion transport activity of 1,3-bis(benzimidazol-2-yl)benzenes [18] and similar motifs, [19] we adapted Chess ystems and designed and synthesized new switchable cycloaurated putative anion transporters based on the structurally related 1,3-bis(benzimidazol-2-yl)pyrimidine (BisBzImPy).…”
Section: Introductionmentioning
confidence: 91%
“…Nevertheless, over the past four decades of intensive research since the first report on the synthetic transporter in 1982, [11] study on the synthetic membrane transporters has overwhelmingly focused on transport of inorganic cations [12–37] or anions, [38–60] with much less on molecular species such as water [61–71] and glucose [72] . Specific to synthetic amino acid transporters, we are aware of only two artificial transporter systems based on a pillar[5]arene derivative by Hou in 2013 [73] or dynamic covalent bonds by Gale in 2015 [74] …”
Section: Introductionmentioning
confidence: 99%